AWIG-AWIG - AWAG-AWAG-UWUG: SEBUAH SOLUSI SEDERHANA DITENGAH SEMARAKNYA UPACARA-UPAKARA - Made Aripta Wibawa (Sanjiwani: Jurnal Filsafat, 2018)
Almost simbolism Hindu religion in Bali has a supernatural power that sthrengthen at the roots to be manifested as Hindu culuture identity. Rites and ritual as banten, kajang, tedung, and umbul-umbul as manfensted Yantra, Tantra and Mantra . Like a stage body corpse as a tool to be lifted to cemestry the symbol off the spirit will go to heaven. Even a clan is a very identity on rites and performing Bali colourful without stoping, and glamour as well. But also the essence of ritual did not understand as long by the understanding philoshopy.